Effects of physical characteristics of carbon black on metabolic regulation in mice. (January 2018) - Chuang, Hsiao-Chi; Hsiao, Ta-Chih; Lee, Chii-Hong; Chun-Te Lin, Justin; Chuang, Kai-Jen; Feng, Po-Hao; Cheng, Tsun-Jen
Abstract: Potential adverse effects of human exposure to carbon black (CB) have been reported, but limited knowledge regarding CB-regulated metabolism is currently available. To evaluate how physical parameters of CB influence metabolism, we investigated CB and diesel exhaust particles (DEPs) and attempted to relate various physical parameters, including the hydrodynamic diameter, zeta potential, and particle number concentrations, to lung energy metabolism in female BALB/c mice. A body weight increase was arrested by 3 months of exposure to CB of smaller-size fractions, which was negatively correlated with pyruvate in plasma. There were no significant differences in cytotoxic lactate dehydrogenase (LDH) or total protein in bronchoalveolar lavage fluid (BALF) after 3 months of CB exposure. However, we observed alterations in acetyl CoA and the NADP/NADPH ratio in lung tissues with CB exposure. Additionally, the NADP/NADPH ratio was associated with the zeta potential of CB. Mild peribronchiovascular and interstitial inflammation and multinucleated giant cells (macrophages) with a transparent and rhomboid appearance and containing foreign bodies were observed in lung sections. We suggest that physical characteristics of CB, such as the zeta potential, may disrupt metabolism after pulmonary exposure. These results, therefore, provide the first evidence of a link between pulmonary exposure to CB and metabolism. Graphical abstract: Highlights: We evaluated how physical parameters of CB influence metabolism in mice lungs. Body weight was arrested by exposure to CB in mice. CB-induced peribronchiovascular and interstitial inflammation in the lungs. Disruption in functions of acetyl CoA and NADP/NADPH was observed in lungs. NADP/NADPH ratio was associated with the zeta potentials of CB.